Finite element modelling analysis on built-up column - Candra, Menan Nagappan (2015)
Build-up column is a steel structure composed of two I-beam steel joined with steel plate or angles as the lacings of the column. The build-up column is one of the main load carrying members among all the other structural components of a building. Since the build-up column is assembled manually at the construction site, there might have some error in the section and orientation of the lacings assembled which will affect the performance of the build-up column. The main objectives of this study the effect of the different section and orientation of steel elements on build-up column in terms of buckling and stress distribution. Finite Element Analysis of Ansys 12.0 software is used to design the ten model of the build-up column. In order to study the effect of section of lacings, steel plate and L-angles are used. Besides that, to study the effect of orientation of the lacings, inclination angles of 40° , 45°, 50° , 55 ° and 60° are used. Based on the results, orientation of the steel lacings influenced the stress distribution of the due to the load. The greater the inclination angle the smaller the stress builds up on the lacings. Thus, the build-up column is more stable